2018
DOI: 10.1142/s0219877018500311
|View full text |Cite
|
Sign up to set email alerts
|

Business Modeling and Public Policy in High-Tech Industries: Exploratory Evidences from Two Brazilian Semiconductor Support Programs

Abstract: This paper adopts an exploratory analysis based on a multiple case study to investigate the interplay of Small and Medium Enterprises (SMEs) business modeling strategies and Science, Technology and Innovation (STI) policies in a mid-income country efforts to develop a national semiconductor industry. Specifically, we analyze how 22 Brazilian SMEs supported by two comprehensive federal programs designed and implemented business models and strategies in an attempt to, on the one hand, meet the scope and timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A study by (Da Silva Alves et al, 2018) explored the use of mobile learning in small and medium-sized enterprises (SMEs) in Brazil. They found that implementing mobile learning initiatives in these organizations impacted employee skills, knowledge, and competency development.…”
Section: Msmes In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by (Da Silva Alves et al, 2018) explored the use of mobile learning in small and medium-sized enterprises (SMEs) in Brazil. They found that implementing mobile learning initiatives in these organizations impacted employee skills, knowledge, and competency development.…”
Section: Msmes In Brazilmentioning
confidence: 99%
“…These courses range from technical skills, such as basic accounting and IT, to soft skills, such as effective communication and customer service. In addition, several e-learning platforms in Brazil offer courses tailored to the needs of SMEs (Da Silva Alves et al, 2018). The platform makes it easy for companies to find the required courses and for employees to access them.…”
Section: Msmes In Brazilmentioning
confidence: 99%
“…By analyzing technology development strategies in an AgTech startup, this paper attempted to fill a gap in the literature, given the scarcity of documented similar experiences from developing countries. Such scarcity of academic case studies exploring these themes is, on the one hand, influenced by the reluctance of entrepreneurs in providing information revealing details of the technological approaches underlying their business models (Botelho and Almeida, 2010;Alves, et al, 2018), and on the other hand, by the difficulties of reproducing the findings of a single case study based on exploratory research (Edmondson and McManus, 2007). As regards the first aspect, the company founder is one of the authors of this paper, which guarantees accountability of the information and data disclosed in connection with this research.…”
Section: Introductionmentioning
confidence: 99%
“…By analysing technology development strategies in an AgTech startup, this chapter attempts to fill a gap in the literature, given the scarcity of documented similar experiences from developing countries. Such scarcity of academic case studies exploring these themes is, on the one hand, influenced by the reluctance of entrepreneurs in providing information revealing details of the technological approaches underlying their business models (Botelho and Almeida, 2010;Alves, et al, 2018). On the other hand, by the difficulties of reproducing the findings of a single case study based on an exploratory research (Edmondson and McManus, 2007).…”
Section: Introductionmentioning
confidence: 99%